Special Autonomy Papua: Compliance Against Applicable Rules/Guidelines (Case Study In Jayapura City) - Purwadi, Marsi Adi (Faculty of Law Cenderawasih University, 2017)
The main purpose of this study is to identify and analyze the implementation of activities financed by the Special Autonomy Fund whether it is in accordance with existing rules/guidelines, whether it is seen from the routine activities, the funds used in each activity, the leverage of the implementation of activity towards the achievement the vision and mission of the regional head, the involvement of the Papuans in the activities, and the influence of the implementation of the activities towards solving the problems of the Local people. Methods used include: Quantitative descriptive statistics in the form of concentration measures, and crosstab analysis. Based on the results of this study it can be concluded that: 1) During the period of 2008-2014 the implementation of programs/activities classified routinely carried out all almost been implemented with reference to the rules / guidelines of the implementation of Special Autonomy in Papua Province; 2) Development Programs /Activities implemented through the use of Special Autonomy funds, indicating the amount of activities that use substantial amount of funds and the implementation is in accordance with the rules/guidelines of the implementation of Special Autonomy in Papua Province; 3) Implementation of development activities using Special Autonomy funds in Jayapura City has been able to play a role in improving the achievement of vision and mission of regional head, whose implementation has been in accordance with existing rules/guidelines; 4) The results of this study indicate that many programs/activities involving the implementation of many Orang Asli Papua, whose implementation has been in accordance with existing rules/guidelines; 5) Implementation of Special Autonomy policy in Papua Province is expected to solve the problems faced by Orang Asli Papua. The results of this study indicate that most of the activities undertaken by the Jayapura City Government using Special Autonomy funds have had an impact/change in alleviating the problems/problems faced by Local People, whose implementation has been in accordance with existing rules/guidelines.